2022
DOI: 10.1155/2022/6979117
|View full text |Cite
|
Sign up to set email alerts
|

lnc-MRGPRF-6:1 Promotes M1 Polarization of Macrophage and Inflammatory Response through the TLR4-MyD88-MAPK Pathway

Abstract: Background. Macrophage-mediated inflammation plays an essential role in the development of atherosclerosis (AS). Long noncoding RNAs (lncRNAs), as crucial regulators, participate in this process. We identified that lnc-MRGPRF-6:1 was significantly upregulated in the plasma exosomes of coronary atherosclerotic disease (CAD) patients in a preliminary work. In the present study, we aim to assess the role of lnc-MRGPRF-6:1 in macrophage-mediated inflammatory process of AS. Methods. The correlation between lnc-MRGP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It was reported that the injury of macrophages in AS was associated with ferroptosis [ 32 ]. In our previous study, it was demonstrated that lnc-MRGPRF-6:1 was highly expressed in CAD patients and could mediate macrophage polarization to promote inflammation progression in AS [ 5 ]. In the present study, it was demonstrated that ox-LDL-induced macrophage ferroptosis and lnc-MRGPRF-6:1 could promote ox-LDL-induced macrophage ferroptosis in AS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the injury of macrophages in AS was associated with ferroptosis [ 32 ]. In our previous study, it was demonstrated that lnc-MRGPRF-6:1 was highly expressed in CAD patients and could mediate macrophage polarization to promote inflammation progression in AS [ 5 ]. In the present study, it was demonstrated that ox-LDL-induced macrophage ferroptosis and lnc-MRGPRF-6:1 could promote ox-LDL-induced macrophage ferroptosis in AS.…”
Section: Discussionmentioning
confidence: 99%
“…As is known to all, inflammatory progression is essential basis of AS [ 4 ]. Macrophage-mediated inflammation plays an important role in the pathophysiology of AS [ 5 ]. The progression of inflammation is closely associated with cell death [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have indicated that exosomes can be used as carriers of lncRNA to regulate cellular activities of neighboring cells. The upregulation of lnc-MRGPRF-6:1 expression and as its correlation with levels of proinflammatory mediators have been detected in the plasma exosomes of patients with CAD [67]. The expression level of lnc-MRGPRF-6:1 following M1 induction was higher than that following M2 induction in THP-1 cells.…”
Section: Lncrnas Functioning Via Exosomes In Atherogenesismentioning
confidence: 97%
“…For example, EV’s resealed by endothelial progenitor cells promote M2 macrophage polarization by suppressing miR-9-5p on SIRT1 through the transfer on lncRNA taurine upregulated gene 1 (TUG1), an important lncRNA that is downregulated during sepsis ( 44 ). In patients with coronary atherosclerosis, EVs carrying lncRNA-MRGPRF-6:1 promote M1 macrophage polarization by activating TLR4, myeloid differentiation factor-8, and mitogen-activated protein kinase (TLR4-MyD88-MAPK) ( 45 ). Also, blockade of lnc-RNA-ASLNCS5088-enriched EVs dampens the effect of M2 macrophages in fibroblast activation ( 46 ).…”
Section: Potential Interactions Of Extracellular Vesicles and Immune ...mentioning
confidence: 99%